Palla Strozzi, a Florentine merchant-banker in Lyon: Financial power, trade networks, global warfare and internal struggles during the Italian wars - Michele Maria Rabà (The Journal of European Economic History (JEEH), 2025)
The essay examines the commercial and financial activities of Palla Strozzi, a Florentine merchant active in Lyon in the first half of the 16th century. A cousin of the leaders of the Florentine republican movement - the brothers Piero, Roberto and Leone Strozzi, allies of France against duke Cosimo Medici and his protector, emperor Charles V of Habsburg -, Palla provided relevant financial services to both the Valois and his relatives exiled from their homeland and declared rebels, while maintaining excellent relations with the Medici's power. As an eminent member of the Florentine Diaspora abroad, Palla was fully integrated in that trade network that ensured Florence's prosperity within the highly integrated Euro-Mediterranean economic area, thanks to the extensive resort to the most advanced instruments of credit. This network enabled the flow of the capitals intended to support the war effort of the struggling European powers, as well as of the money needed to move goods within import and export operations. Neither Duke Cosimo Medici, nor Emperor Charles V, nor the king of France could therefore prosecute their subject merchants who cooperated financially with the enemy without compromising the flow of merchandise, scriptural money and cash that made it possible to control the price of primary goods and to collect considerable revenue by taxing products in transit.
Keywords: 330; Bankmanager; Kaufleute; Unternehmensnetzwerk; Wirtschaftliche Macht; Krieg; Wirtschaftsgeschichte; Lyon; Italien